Assessing climate and health curriculum in graduate public health education in the United States - Arora, Mona; Comrie, Andrew C.; Ernst, Kacey E. (Frontiers in Public Health, 2023)
Climate change has been identified as both a challenge and an opportunity for public health. The onus to prepare the next generation of public health practitioners lies heavily on schools and programs of public health. This article (i) assesses the status of climate change and health curricula in accredited schools of public health in the United States and (ii) proposes strategies to better train professionals so they are more informed and prepared to mitigate, manage, and respond to the health impacts of climate change. Course offerings and syllabi listed in online course catalogs from 90 nationally accredited schools of public health were evaluated May-July 2018 with the purpose of identifying the extent of climate change education in graduate programs. Only 44 public health institutions were found to offer a climate change related course at the graduate level of education. Of the 103 courses identified, approximately 50% (n=46) are focused on this topic. These courses cover a wide array of topics with an emphasis on conveying fundamental concepts. In-depth assessment revealed a need for integrating learning opportunities that build practical skills useful in a hands-on public health practice environment. This assessment indicates the limited availability of climate-health course offerings available to graduate students in accredited schools. The findings are used to propose an educational framework to integrate climate change into public health curricula. The proposed framework, while rooted in existing directives, adopts a tiered approach that can be readily applied by institutions training the next generation of public health leaders.